Effect of stereosequences on crystallinity and properties of zone-drawn poly(vinyl alcohol) microfibrils - Lyoo, WS; Kim, JH; Koo, K; Lee, JS; Kim, SS; Yoon, WS; Ji, BC; Kwon, IC; Lee, CJ (JOHN WILEY & SONS INC, 2001)
To effectively orient the molecular chains of novel syndiotactic poly(vinyl alcohol) (PVA) microfibrillar fiber (PVA fibril), a high-temperature zone-drawing method was adopted. The PVA fibrils were directly prepared from the saponification and in situ fibrillation without a spinning procedure. The maximum draw ratio of the PVA fibril increased with a decrease in the syndiotactic diad (r-diad) content, indicating that the deformability of WA molecules was lowered in higher syndiotactic PVA. Degree of crystal orientations up to 0.990 were achieved by stretching the PVA fibril with the r-diad content of 65.1% and the original degree of crystal orientation of 0.902 at 250 degreesC close to its crystal melting temperature (T,). When the same draw ratio was applied to the fibrils, a higher crystal orientation was achieved for the fibrils having higher syndiotacticity. Wide-angle X-ray data show that the longitudinal crystal sizes of drawn PVA fibrils were larger in higher syndiotacticities. The degree of crystal orientation, crystallinity, T,, longitudinal crystal size, and tensile strength of the maximum drawn WA fibril with a r-diad content of 65.1% were 0.99, 0.97, 279 degreesC, 187 Angstrom, and 4.66 N/tex, respectively. (C) 2001 John Wiley & Sons, Inc.
Keywords: OPTIMUM POLYMER CONCENTRATION; AROMATIC POLYAMIDE FILM; POLYETHYLENE GEL FILM; MOLECULAR-WEIGHT; HIGH-STRENGTH; TENSILE-STRENGTH; CROSS-LINKING; FIBERS; SAPONIFICATION; POLYVINYL-ALCOHOL)